Pictorial Representation of Illness and Self‐Measure to assess the perceived burden in patients with chronic inflammatory vulvar diseases: an observational study. (29th June 2020) - Corazza, M.; Virgili, A.; Toni, G.; Valpiani, G.; Morotti, C.; Borghi, A.
Abstract: Background: Chronic inflammatory vulvar diseases can have a huge detrimental impact on patient welfare. A few studies have addressed this issue so far, mainly measuring patients' quality of life or sexual dysfunction. Objective: To assess the burden of suffering in patients with chronic inflammatory vulvar diseases using the Pictorial Representation of Illness and Self‐Measure (PRISM), a visual, non‐verbal instrument. We also assessed (i) the concordance between PRISM and the Dermatology Life Quality Index (DLQI), (ii) whether some variables, both patient‐related and disease‐related, affect the patient's suffering and quality‐of‐life impairment. Methods: We evaluated for inclusion in this cross‐sectional study all patients who attended our Vulva Unit over a 9‐month period with histologically proven lichen sclerosus (LS), lichen planus (LP), lichen simplex chronicus (LSC), eczema, plasma cell vulvitis and psoriasis (at least five for each disease). Demographics and disease‐related subjective and objective scores were recorded. The PRISM and DLQI were administered. Results: We included 87 patients affected with LS, 13 with LSC and seven with LP. Median PRISM values (0–273 mm) ranged from 95 to 120 mm, depending on the disease, and median DLQI scores (0–30) were five for all three groups. Neither PRISM nor DLQI scores differed significantly among the three groups. Moderate coherence was found between PRISM and DLQI (ρ = 0.5455, P  < 0.001). Global subjective score was the only variable significantly associated with the degree of suffering and quality‐of‐life impairment. Conclusions: Pictorial Representation of Illness and Self‐Measure proved to be a valuable, highly reliable tool for measuring the perceived burden in these patients. In spite of a moderate correlation, PRISM resulted more sensitive in capturing patient distress than DLQI.